Relationship of depth of invasion to survival outcomes and patterns of recurrence for T3 oral tongue squamous cell carcinoma. (May 2021) - Newman, M.; Dziegielewski, P.T.; Nguyen, N.T.A.; Seikaly, H.S.; Xie, M.; O'Connell, D.A.; Harris, J.R.; Biron, V.L.; Gupta, M.K.; Archibald, S.D.; Jackson, B.S.; Young, J.E.M.; et al.
Highlights: DOI is an independent predictor of poor survival outcomes in pT3N0M0 OTSCC patients. Based on DOI, two prognostic groups may exist within the 8th Ed AJCC pT3N0M0 stage. DOI (10–20 mm) has worse overall and disease-specific survival than DOI (≤10 mm). DOI (10–20 mm) had more regional recurrence, especially in the contralateral neck. Abstract: Introduction: Current research is elucidating how the addition of depth of invasion (DOI) to the 8th edition of the American Joint Committee on Cancer (AJCC) TNM staging for oral cavity squamous cell carcinoma influences its prognostic accuracy. However, there is limited research on survival in pT3N0M0 oral tongue SCC (OTSCC) patients when stratifying by DOI. Objectives: Determine 5-year overall survival (OS), and cancer-specific survival (CSS) for patients with pT3N0M0 oral OTSCC based on shallow DOI (<10 mm) and deep DOI (10–20 mm). Methods: Retrospective review involving three tertiary care cancer centers in North America. cT3N0M0 OTSCC patients receiving primary surgical treatment from 2004 to 2018 were identified. Inclusion: age > 18 years old and confirmation of pT3N0M0 OTSCC on surgical pathology. Exclusion: patients undergoing palliative treatment or previous head and neck surgery/radiotherapy. Analysis comprised two groups: shallow pT3 (tumor diameter > 4 cm, DOI < 10 mm) and deep pT3 (DOI 10 mm-20 mm). Results: One hundred and four patients with pT3N0M0 OTSCC were included. Mean age was 59.1 years (range: 18–80.74). Age, gender, and Charlson Comorbidity Index were similar between the two groups (p > 0.05). Recurrence, LVI, PNI, and positive margins were more common in deep T3 tumors (P < 0.05). 5-year OS (50% vs 26%, p = 0.006) and CSS (72% vs 24%, p = 0.005) were worse in deep pT3 tumors. Deep pT3 disease was an independent predictor of OS (p = 0.004) and CSS (p = 0.01) on Cox-Regression analysis. Conclusion: DOI is an independent predictor of poor survival in pT3N0M0 OTSCC patients. Consideration should be given to escalating adjuvant therapy for deep pT3N0M0 OTSCC patients.